Fat Content Modulates Rapid Detection of Food: A Visual Search Study Using Fast Food and Japanese Diet - Sawada, Reiko; Sato, Wataru; Toichi, Motomi; Fushiki, Tohru (Frontiers in Psychology, 2017)
Rapid detection of food is crucial for the survival of organisms. However, previous visual search studies have reported discrepant results regarding the detection speeds for food versus non-food items; some experiments showed faster detection of food than non-food, whereas others reported null findings concerning any speed advantage for the detection of food versus non-food. Moreover, although some previous studies showed that fat content can affect visual attention for food, the effect of fat content on the detection of food remains unclear. To investigate these issues, we measured reaction times (RTs) during a visual search task in which participants with normal weight detected high-fat food (fast food), low-fat food (Japanese diet), and non-food (kitchen utensils) targets within crowds of non-food distractors (cars). Results showed that RTs for food targets were shorter than those for non-food targets. Moreover, the RTs for high-fat food were shorter than those for low-fat food. These results suggest that food is more rapidly detected than non-food within the environment and that a higher fat content in food facilitates rapid detection.